Optimum route selection in hole-making operations using a dynamic programming-based method. Issue 1 (31st December 2016) - Solimanpur, Maghsoud; Foroughi, Ahad; Mohammadi, Mehran
Abstract: Hole-making is a type of machining processes that are specifically used to cut a hole into a part. The objective of interest in hole-making operations is to reduce the summation of tool airtime and tool switching time in order to reduce total processing time. This objective is affected by the sequence through which operations are done. This problem is formulated as a zero–one nonlinear mathematical programming model. In this paper, a dynamic programming-based method is developed to solve the proposed mathematical model and obtain the globally optimum solutions. An illustrative example is given to show the application and efficiency of the proposed method for optimizing the sequence of hole-making operations in a typical industrial part. The quality of solutions obtained by the proposed method is compared to those obtained by both branch-and-bound method and an ant algorithm available in the literature. The computational experiments reflect the high efficiency of our proposed method.